A Tunable Dual-Band Metamaterial Absorber for Terahertz Applications - Nikhil N.B.; Nair B.R.; Philip A.; Nilotpal; Mohamed A.; Saha C.; Bhattacharyya S. (My University, 2025)
A tunable dual-band metamaterial absorber for terahertz range operation is illustrated in this paper. The tunability can be attained using the variable resistive property of diodes in reverse bias operation. The absorption bands are observed at ~45 μm (6.719 THz) and ~80 μm (3.765 THz). The structure exhibits variation in absorptivity with the variation in the resistance of diode. The proposed structure is with the dimensions having a periodicity of (~λ/4) and the thickness of (~λ/53). The tunable dual-band metamaterial absorber can have potential applications in the area of sensing, stealth technology, etc. © 2021, Springer Nature Singapore Pte Ltd.